Rokat Tèkos Jhâghung (Ritual of Repellent of Maize-Eating Rats in East Madura: A Phenomenological Study) - Mohammad Hefni (Institut Agama Islam Negeri Madura, 2017)
East Madura, ie Pamekasan and Sumenep regencies, has an agricultural pattern that focuses on dry ecology. Therefore, the area is very suitable for the cultivation of maize crops. Various efforts have been made to improve the productivity of maize, both in terms of natural resource management and human resource improvement. This paper presents an another attempt, namely the supernatural effort through the rokat tèkos jhâghung ritual believed by the local farmers that it was able to repel maize-eating rats so that the productivity of maize will increase. This qualitative research conducted in Taghedhân kampung, Airmera Village, Sumenep by using the social theory of phenomenology, resulted in the finding that the rokat tèkos jhâgung ritual is a ritual of petition to Allah Almighty so that the maize crops of the village community are not encroached by the rats with the spiritual help of tarètan sè empa' (the four sisters), ie Sariyâ as a symbol of aèng kabâ (amniotic fluid), Nuriyâ as a symbol of tamonè (placenta), Bhuwana as a symbol of tontonan (umbilical cord), and Bhuwani as a symbol of dârâ (blood). This effort provides an alternative to the expulsion of rat pests that damage crops from rice fields, after previously there is a natural effort in expelling rat pests from rice fields in Bali through the recording of gamelan blaganjur sounds. Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i2.1378